Olympia, Griechenland. Das Leonidaion. Die Arbeiten der Jahre 2016 bis 2018 - Mächler, Claudia (e-Forschungsberichte des DAI, 2019)
After already having published a preliminary report on the campaigns in 2014 and 2015, this series shall be continued by a summary of the work performed between 2016 and 2018. During this period the building survey could be finished, over 1000 workpieces were assigned to the Leonidaion, a structure from motion based 3D-model was created and the trial trenches that complemented the mere survey proved to be of great importance, since they shed new light on the dating of the so-called first Roman Imperial refashioning of the Leonidaion.